European Society of Cardiology/Heart Failure Association position paper on the role and safety of new glucose‐lowering drugs in patients with heart failure. (9th December 2019) - Seferović, Petar M.; Coats, Andrew J.S.; Ponikowski, Piotr; Filippatos, Gerasimos; Huelsmann, Martin; Jhund, Pardeep S.; Polovina, Marija M.; Komajda, Michel; Seferović, Jelena; Sari, Ibrahim; Cosentino, Francesco; Ambrosio, Giuseppe; et al.
ABSTRACT: Type 2 diabetes mellitus (T2DM) is common in patients with heart failure (HF) and associated with considerable morbidity and mortality. Significant advances have recently occurred in the treatment of T2DM, with evidence of several new glucose‐lowering medications showing either neutral or beneficial cardiovascular effects. However, some of these agents have safety characteristics with strong practical implications in HF [i.e. dipeptidyl peptidase‐4 (DPP‐4) inhibitors, glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA), and sodium–glucose co‐transporter type 2 (SGLT‐2) inhibitors]. Regarding safety of DPP‐4 inhibitors, saxagliptin is not recommended in HF because of a greater risk of HF hospitalisation. There is no compelling evidence of excess HF risk with the other DPP‐4 inhibitors. GLP‐1 RAs have an overall neutral effect on HF outcomes. However, a signal of harm suggested in two small trials of liraglutide in patients with reduced ejection fraction indicates that their role remains to be defined in established HF. SGLT‐2 inhibitors (empagliflozin, canagliflozin and dapagliflozin) have shown a consistent reduction in the risk of HF hospitalisation regardless of baseline cardiovascular risk or history of HF. Accordingly, SGLT‐2 inhibitors could be recommended to prevent HF hospitalisation in patients with T2DM and established cardiovascular disease or with multiple risk factors. The recently completed trial with dapagliflozin has shown a significant reduction in cardiovascular mortality and HF events in patients with HF and reduced ejection fraction, with or without T2DM. Several ongoing trials will assess whether the results observed with dapagliflozin could be extended to other SGLT‐2 inhibitors in the treatment of HF, with either preserved or reduced ejection fraction, regardless of the presence of T2DM. This position paper aims to summarise relevant clinical trial evidence concerning the role and safety of new glucose‐lowering therapies in patients with HF.